Bulk-fill composite marginal adaptation evaluated by cross-polarization optical coherence tomography. Issue 1 (1st January 2019) - Turkistani, Alaa; Ata, Areej; Alhammad, Raghad; Ghurab, Raneem; Alahmadi, Yusra; Shuman, Muhaned; Jamleh, Ahmed; Naguib, Ghada; Bakhsh, Turki
Abstract: Objective: This study evaluated interfacial gap formation in bulk-fill composite restorations using cross-polarization optical coherence tomography (CP-OCT). Materials and methods : Two bulk-fill resin composite materials each with its specific adhesive were used; light-cured Filtek Bulk Fill Posterior Restorative with Scotchbond Universal (3M ESPE) "group A" and dual-cure bulk-fill composite BulkEZ with Prelude One (Danville Materials) "group B." Proximal cavities (2 × 2 × 4.5 mm; width × length × depth) prepared on extracted human molars ( n = 5) were restored with adhesives applied in self-etch mode and the composite placed in bulk. After 24 h storage, the specimens were immersed in ammoniacal silver nitrate solution for 24 h followed by a photo-developing solution for 8 h. Later, CP-OCT (Santec, Japan) at 1310 nm center wavelength was used to scan each specimen. Interfacial gap at the gingival floor was analyzed on cross-sectional OCT images obtained from each specimen at 0.5 mm interval using ImageJ analysis software. Result : Mann–Whitney test showed a significant difference ( p < 0.05) between the groups with group A showing higher percentage of gap formation at the gingival floor. Conclusion : Within the limitation of the study, a better sealing of gingival margin was achieved with the dual-cure bulk-fill dental composite compared to the light-cured composite.